2020
DOI: 10.1108/bij-07-2020-0380
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of green advertising – a review of literature and bibliometric analysis

Abstract: PurposeThe purpose of this paper is to present an overview of the research which has been done during the past three decades on the topic of green advertising and identify gaps for future research.Design/methodology/approachThe methodology that has been adopted for analysis is two-pronged – the first being a literature review with tabulation of data using excel sheets and bar graphs and the second being a bibliometric review using the software VOSviewer. Both approaches analyze the number of citations, keyword… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 138 publications
(88 reference statements)
0
35
0
Order By: Relevance
“…Kirmani and Khan (2016) suggests that more studies are needed on green marketing from developing countries, including China, India, etc. Similarly, Agarwal and Kumar (2020) found that most studies in green marketing are from the United States based on three decades of literature. Therefore they also suggested having more studies from other countries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kirmani and Khan (2016) suggests that more studies are needed on green marketing from developing countries, including China, India, etc. Similarly, Agarwal and Kumar (2020) found that most studies in green marketing are from the United States based on three decades of literature. Therefore they also suggested having more studies from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…We have responded to Kimmai's future research direction by studying Pakistan because it is a developing country and has serious environmental degradation problems. Similarly, Agarwal and Kumar (2020), based on three decades of literature bolometric review, found that most green advertising studies are from the United States. Therefore they felt more studies are needed the other countries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations